2004
DOI: 10.1007/s10620-004-9580-5
|View full text |Cite
|
Sign up to set email alerts
|

Coinfection: Helicobacter pylori/Human Immunodeficiency Virus

Abstract: To compare H. pylori infection prevalence and gastric mucosa damage in HIV-infected and non-HIV-infected patients, gastric biopsies were systematically taken in 209 individuals who underwent upper Gl endoscopy (102 HIV-infected and 107 non-HIV-infected). H. pylori was found in 42 (41.1%) HIV-infected patients and in 53 (49.5%) non-HIV patients (P = 0.22, chi2 = 1.47, NS). In HIV-positive patients infected with H. pylori the mean CD4 count was higher than in HIV-positive patients without H. pylori (364 and 228 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
27
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 29 publications
7
27
0
Order By: Relevance
“…We did not find statistically significant associations between AIDS or C3 stage of HIV infection and the presence of Helicobacter pylori. However, there was a negative (OR=0.40), though not statistically significant association between CD4+ T-lymphocytes level < 200 cells/µL and Helicobacter pylori infection, which concurs to the tendency described in literature (2,5).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We did not find statistically significant associations between AIDS or C3 stage of HIV infection and the presence of Helicobacter pylori. However, there was a negative (OR=0.40), though not statistically significant association between CD4+ T-lymphocytes level < 200 cells/µL and Helicobacter pylori infection, which concurs to the tendency described in literature (2,5).…”
Section: Discussionsupporting
confidence: 89%
“…Lower prevalence of Helicobacter pylori infection was noticed at CD4+ T-lymphocyte levels below 200cells/µL (5). Other studies depicted a reduction in the frequency of Helicobacter pylori infection among severely immunosuppressed patients, with acquired immunodeficiency syndrome (AIDS) (2,3,5,(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reasons for these lower rates of H pylori infection remain unclear. Other studies showed that H pylori infection is similar in both HIV-positive and HIV-negative patients [12,13] . Patients infected with HIV, with or without acquired immune deficiency syndrome (AIDS), have a high incidence (50%-90%) of upper gastrointestinal symptoms [14] .…”
Section: Introductionmentioning
confidence: 99%
“…26,[39][40][41] As regards HIVpositive subjects, the prevalence of H. pylori infection seems not to be different from that in HIV-negative subjects, 36,42 but it has been observed that the histological score of H. pylori-gastritis was more severe in HIV-positive subjects. 43 Thus, the results of this review suggest that the impaired absorption of thyroxine, L-dopa and delavirdine associated with H. pylori infection may have potentially relevant clinical implications, because these drugs are often used in disorders in which the co-presence of H. pylori infection seems to be frequent and ⁄ or severe. A further finding which emerged from the present review was that one of the likely pathophysiological mechanisms for impaired drug absorption associated with H. pylori infection seems to be reduced gastric acid secretion.…”
Section: Discussionmentioning
confidence: 98%